x 4 *cos(x)
d / x \ --\4 *cos(x)/ dx
Применяем правило производной умножения:
ddxf(x)g(x)=f(x)ddxg(x)+g(x)ddxf(x)\frac{d}{d x} f{\left(x \right)} g{\left(x \right)} = f{\left(x \right)} \frac{d}{d x} g{\left(x \right)} + g{\left(x \right)} \frac{d}{d x} f{\left(x \right)}dxdf(x)g(x)=f(x)dxdg(x)+g(x)dxdf(x)
f(x)=4xf{\left(x \right)} = 4^{x}f(x)=4x; найдём ddxf(x)\frac{d}{d x} f{\left(x \right)}dxdf(x):
ddx4x=4xlog(4)\frac{d}{d x} 4^{x} = 4^{x} \log{\left(4 \right)}dxd4x=4xlog(4)
g(x)=cos(x)g{\left(x \right)} = \cos{\left(x \right)}g(x)=cos(x); найдём ddxg(x)\frac{d}{d x} g{\left(x \right)}dxdg(x):
Производная косинус есть минус синус:
ddxcos(x)=−sin(x)\frac{d}{d x} \cos{\left(x \right)} = - \sin{\left(x \right)}dxdcos(x)=−sin(x)
В результате: −4xsin(x)+4xlog(4)cos(x)- 4^{x} \sin{\left(x \right)} + 4^{x} \log{\left(4 \right)} \cos{\left(x \right)}−4xsin(x)+4xlog(4)cos(x)
Теперь упростим:
4x(log(4cos(x))−sin(x))4^{x} \left(\log{\left(4^{\cos{\left(x \right)}} \right)} - \sin{\left(x \right)}\right)4x(log(4cos(x))−sin(x))
Ответ:
x x - 4 *sin(x) + 4 *cos(x)*log(4)
x / 2 \ 4 *\-cos(x) + log (4)*cos(x) - 2*log(4)*sin(x)/
x / 3 2 \ 4 *\log (4)*cos(x) - 3*log (4)*sin(x) - 3*cos(x)*log(4) + sin(x)/